Por uma geografia da crise? - Arruda Boechat, Cássio; Teixeira Pitta, Fábio; Gonçalves Leite, Ana Carolina; Jones Kluck, Erick Gabriel; Manzione Giavarotti, Daniel; de Campos Silva, Allan Rodrigo; de Almeida Toledo, Carlos (Geografares, 2019)
Editorial.